Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Kontekstual Pada Muatan Pelajaran IPA Kelas V Sekolah Dasar - Widiastuti, Ni Luh Gede Karang; Priantini, Dewa Ayu Made Manu Okta (Universitas Pendidikan Ganesha, 2022)
The lack of students’ worksheet that is able to encourage students to make connections between their knowledge and its application in everyday life. In addition, the utilization of supplementary students’ worksheet was still lacking, it only based on the government students’ worksheet. This study aimed to develop contextual-based worksheets on the content of science lessons for fifth grade elementary school, especially on the 5th theme and 2nd sub-theme. The research method used was research and development with the ADDIE model. The research subjects consisted of material experts, media experts, linguists, and users consisting of students and teachers, meanwhile the object in this research was contextual-based worksheets on the science lessons content. The data collection method used was the non-test method, by using an instrument in the form of a questionnaire. The data analysis technique used descriptive statistical data analysis. The results showed that the contextual-based students’ worksheet on the science lesson content developed has fulfilled very feasible criteria from the validation results of media experts, material experts, and linguists with an average score of 89.1%. The test of teacher and student responses to the use of students’ worksheet obtained 88.3% and 87.55% scores. The conclusion of this research was that the contextual-based students’ worksheet on the content of science lessons developed has met the very feasible and interesting criteria to be used. The implications of this research could help students to understand the material in the learning process, therefore learning objectives could be achieved.